Effects of moisture and fermentation length on the quality and digestibility of fermented concentrate using tamanu kernel cake as the main protein source through an in vitro study. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The present study aimed to evaluate the effects of moisture and fermentation length on the chemical compositions, fermentation characteristics, feed-out phase, and ruminal digestibility of fermented concentrate using tamanu kernel cake (TKC) as the main protein source. Materials and Methods: The concentrate was formulated to contain 16.5% crude protein (CP) and 35% neutral detergent fiber consisting of 40% TKC, 7.60% soybean meal, 25.0% wheat pollard, 26.4% dried cassava, and 1% molasses. Those ingredients were mixed and fermented anaerobically at 5 kg into a vacuumed plastic bag with different additional sterile distilled water to reach moisture levels at 25% (MO25), 35% (MO35), and 45% (MO45). Each moisture level was incubated with different fermentation lengths consisting of 2, 7, 14, 21, and 42 days in quadruplicate. After fermentation, each silo was sub-sampled for laboratory analyses. Results: MO25 and MO35 led to higher CP with lower acid detergent fiber than MO45. In the fermentation, MO35 and MO45 generated higher (p < 0.05) lactate than MO25. An extended fermentation length linearly dropped (p < 0.05) dry matter, CP, and ether extract, but gradually increased (p < 0.05) ammonia-N, lactate, acetate, and the counts of lactic acid bacteria, yeast, and bacilli. After 42 days, MO25 and MO35 initiated higher (p < 0.05) aerobic stability. The digestibility and total volatile fatty acid (VFA) in the rumen increased (p < 0.05) over 2 days. However, prolonged fermentation length linearly decreased (p < 0.05) total VFA and methane emission without affecting rumen pH, ammonia-N, and each VFA profile. Conclusion: The application of MO35 was found to reduce nutrient loss and improve aerobic stability comparable to MO25 while achieving fermentation quality similar to MO45, and short-term fermentation, such as 2 days, could improve ruminal digestibility.J. Adv. Vet. Anim. Res., 12(2): 433–444, June 2025http://doi.org/10.5455/javar.2025.l910